Preventive Maintenance Chip Mounter Machine Juki Ke-2070m di PT. Global Jaya Elektronik - Taufik Alfiansyah; Mustofa Abi Hamid (Jurnal Sains dan Teknologi, 2024)
SMT (Surface Mount Technology) is an automatic technology used in the installation of electronic components on a PCB (Printed Circuit Board). There are 3 stages in the manufacture of PCB boards with SMD components, namely Solder Paste, Chip Mounter Machine and Reflow Oven. Chip Mounter Machine is equipment used in the installation of SMD components on a PCB board or can be called a Pick and Place machine. This Chip Mounter Machine is an important piece of equipment in the SMT line, because this machine is the axis in the production of PCB board modules. Therefore, maintenance is carried out to maintain this Chip Mounter Machine so that it can continue to be used. The maintenance carried out is preventive maintenance or preventive maintenance, which aims to prevent unexpected damage to the machine and determine the conditions that cause damage to the machine when the machine is operating. Preventive maintenance carried out includes inspection, cleaning and repair of equipment that is carried out in a planned manner within a certain period of time.